Distribution of non-native Pacific oyster Magallana gigas (Thunberg, 1793) along the eastern Adriatic coast - Ezgeta-Balić, Daria; Šegvić Bubić, Tanja; Stagličić, Nika; Lin, Yaping; Bojanić Varezić, Dubravka; Grubišić, Leon; Briski, Elizabeta (2019)
Non-native Pacific oyster Magallana gigas (Thunberg, 1793) was introduced to the Mediter-ranean Sea for aquaculture purposes in the 1960s. Although this species was not introduced for aquaculture to the Croatian part of the Adriatic Sea, in the 1970s, it was reported in the Lim Bay, in the North-eastern Adriatic. Until recently, there has been no research on the species in the Croatian part of the Adriatic. The aim of this research was to summarize existing and novel data on the distribution of M. gigas in coastal areas of the Eastern Adriatic and to provide a baseline for the future monitoring and assessment programmes of the species. Distribution of M. gigas was determined by three different methods: (i) a visual census of the presence of M. gigas specimens in the medio-littoral zone; (ii) DNA identification of M. gigas larvae in the water column; and (iii) the presence of M. gigas in the subtidal zone at depth between 25 and 40 m. Magallana gigas has a well-established population in the medio-littoral zone of natural and anthropogenic habitats along the coast of the North-eastern Adriatic Sea (west coast of Istria peninsula), but it is not present in the deeper layers . In the Central-eastern and South-eastern Adriatic Sea, the species was either absent or sporadically recorded with no evidence of fully established populations. Considering the great invasion success of M. gigas worldwide and effects that this species could have on the invaded ecosystem (e.g. competition for food and space with native species), detailed future monitoring is needed for the Eastern Adriatic Sea.
Alohtona pacifička kamenica Magallana gigas (Thunberg, 1793) unesena je u akvakulturu Med-iterana 1960tih godina. Iako ova vrsta nije unesena u uzgoj u hrvatskom dijelu Jadrana, 1970tih godina zabilježena je u Limskom zaljevu, sjeverni Jadran. Sve do nedavno kamenica M. gigas nije bila predmet istraživanja na ovom području. Cilj ovog istraživanja bilo je prikazati postojeća i nova saznanja o distribuciji kamenice M. gigas u obalnom dijelu istočnog Jadrana te dati temeljne podatke za budući monitoring i procjenu stanja ove vrste. Rasprostranjenost kamenice M. gigas određivana je primjenom tri metode: (i) vizualni cenzus prisutnosti odraslih primjeraka kamenice M. gigas u mediolitoralnom području; (ii) DNK identifi-kacija ličinki M. gigas u vodenom stupcu; (iii) prisutnost odraslih jedinki M. gigas u ulovu ram-pona. Rezultati su pokazali kako kamenica M. gigas ima dobro razvijene populacije na prirodnim i antropogenim podlogama mediolitorala duž zapadne obale Istre (sjeverni Jadran), ali nije bila prisutna u dubljim slojevima (25 – 40 m). U srednjem Jadranu, pacifička kamenica bila je ili odsutna ili tek sporadično zabilježena bez dokaza da su uspostavljene stabilne populacije. Uzimajući u obzir invazivnost koju je ova vrsta već pokazala diljem svijeta, detaljni monitoring i sustavna istraživanja potrebni su za ovu vrstu duž istočne obale Jadrana.
Bibliografija: str. 144-145.
Summary ; Sažetak.
Keywords: Školjke -- Kamenica -- Magallana gigas -- Invazivne vrste -- Rasprostranjenost -- Monitoring; Jadransko more -- Limski kanal